Implementation of Web-Based Room Management System for Boarding House Operations - Renata Gilang Saputra; Rudi Susanto; Afu Ichsan Pradana (bit-Tech, 2025)
The rapid advancement of digital technologies has significantly impacted various sectors, including property management. However, boarding house management still relies heavily on manual processes, resulting in inefficiencies such as inaccurate tenant data, delayed payments, and difficulties in monitoring room occupancy. This study aims to design and develop a web-based room management information system for Pak Yadi Boarding House, aimed at automating and streamlining key administrative tasks. Using the Waterfall development model, the study follows five phases: requirements analysis, system design, implementation, testing, and maintenance. Data collection was performed through literature review, observation, and interviews with the boarding house owner. The system was implemented using the Laravel framework and MySQL, with system architecture designed using UML diagrams. Testing was conducted using the Black Box method, with user acceptance testing involving one administrator and ten tenants. Key features tested include room data entry, tenant registration, payment invoicing, and complaint management. Results showed that all features performed as intended, and 90% of users expressed satisfaction with the system’s functionality and interface. The system successfully reduced administrative workload, minimized data entry errors, and enhanced operational efficiency. This research demonstrates that web-based systems can improve boarding house management and offers a scalable model for similar small-scale accommodations. Future research could explore integrating mobile access and cloud storage to enhance flexibility and remote management capabilities.